From Supramolecular Vesicles to Micelles: Controllable Construction of Tumor‐Targeting Nanocarriers Based on Host–Guest Interaction between a Pillar[5]arene‐Based Prodrug and a RGD‐Sulfonate Guest. Issue 52 (19th November 2018) - Hu, Xiao‐Yu; Gao, Lei; Mosel, Stefanie; Ehlers, Martin; Zellermann, Elio; Jiang, Hao; Knauer, Shirley K.; Wang, Leyong; Schmuck, Carsten
Abstract: The targeting ability, drug‐loading capacity, and size of the drug nanocarriers are crucial for enhancing the therapeutic index for cancer therapy. Herein, the morphology and size‐controllable fabrication of supramolecular tumor‐targeting nanocarriers based on host–guest recognition between a novel pillar[5]arene‐based prodrugWP5‐DOX and a Arg‐Gly‐Asp (RGD)‐modified sulfonate guestRGD‐SG is reported. The amphiphilicWP5‐DOX ⊃RGD‐SG complex with a molar ratio of 5:1 self‐assembles into vesicles, whereas smaller‐sized micelles can be obtained by changing the molar ratio to 1:3. This represents a novel strategy of controllable construction of supramolecular nanovehicles with different sizes and morphologies based on the same host−guest interactions by using different host−guest ratios. Furthermore, in vitro and in vivo studies reveal that both these prodrug nanocarriers could selectively deliver doxorubicin to RGD receptor‐overexpressing cancer cells, leading to longer blood retention time, enhanced antitumor efficacy, and reduced systematic toxicity in murine tumor model, suggesting their potential application for targeted drug delivery. Abstract : Morphology and size‐controllable supramolecular nanocarriers are developed based on the same host–guest interactions by using different host−guest ratios. The obtained pH‐responsive supramolecular nanocarriers can selectively deliver doxorubicin to RGD receptor‐overexpressing cancer cells, leading to longer blood retention time, enhanced antitumor efficacy, and reduced systematic toxicity in murine tumor model.